Towards sustainable regional economic development : the case study of Iskandar Malaysia - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Bachok, Syahriah (2012)

(untitled)
Regional development is one of the main key players in accelerating the rapid changes and process in Malaysia. Since after the independence, the implementation of the regional development policies and strategies has sped up the urbanization and development including the rapid changes in economic growth. Development of regions emerged due to various reasons including the integration of geography and physical features, the need for cooperation beyond local jurisdiction and also due to the needs of local and national development.